The Prevalence of Elder Abuse in Gorgan and Aq-Qala Cities, Iran in 2013 - Hossien Nassiri; Majideh Heravi Karimooi; Leila Jouybari; Akram Sanagoo; Maryam Chehrehgosha (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Aging and its subsequent issues must be considered as the main challenges of the future. Studies on abuse of the elderly are very limited. This study which was conducted in 2013 and aimed to determine the prevalence and types of domestic abuse in the elderly referred to health care centers in Gorgan and Aq-Qala cities, Gorgan Province, Iran. Methods & Materials: In this cross-sectional analytical study, through a random sampling, 465 elders aged 65 or older (125 men and 254 women), residing in the health care centers in Gorgan and Aq-Qala, were enrolled. A face-to-face interview was carried out with all participants at the health care centers. First, their cognitive states were evaluated using the Iranian version of abbreviated mental test score and if they obtained the score of 6 or higher they would be entered in the study, after taking their informed consents. Then, the domestic elder abuse questionnaire for elderly people and a questionnaire designed by the authors for collecting demographic and personal data was administered. Descriptive (percentage, frequency, mean and standard deviation) and inferential statistics (The Chi-square, t-test) were performed using SPSS (version 16). Results: The total frequency of elder abuse was 63.3%. The highest frequencies were related to care neglect (59.8%) and psychological abuse (53.3%) and the lowest ones belonged to physical abuse (8%) and abandonment (8.2%). Some factors, including sex (P<0.034), ethnicity (P<0.0001), location (P<0.0001), and age (P<0.035) were significantly different between the 2 groups of abused and non-abused. Conclusion: Because of the high level of elder abuse by family, providing awareness programs for seniors, caregivers and health care providers seems to be essential to prevent and reduce the neglect and abuse of older people.